Arendt and Her Human Concerns in the New Age A Critique on the Book Imperialism - Seyed Ali Mahmoudi; Seyed Navid Kalahroudi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main issue of this article is exploring the nature of imperialism as a fundamental phenomenon in new age which is connected to some subjects such as development, nation-state, bureaucracy, and citizenship. The importance and complexity of this issue led Arendt to analyze and critique its multiple aspects. The purpose of this research is the description, analysis and critique of some basic theoretical and historical dimensions of Arendt’s Imperialism and explanation of some aspects of her innovations and shortcomings. The methodology of Thomas A. Spragens on political theorists is used in this research. The outcome of our quest on Arendt’s treatise is that her central problem as a philosopher has been human beings and the ecology of mankind. She has helped for promotion and accuracy of political literature by finding the distinction between definitions of some concepts. In this way, she has clarified the complexities of her treatise. Although she has criticized the humanitarian aid of developed countries to less-developed states and sees it as imperialist, she has not offered a way out of this complex dilemma. To find the cause and analyses of phenomena of the modern age, such as the anti-Semitism and statelessness that Arendt found in racism, are examples of her innovations as a political theorist.